PEMBERDAYAAN MASYARAKAT BERBASIS KOMUNITAS UNTUK PENGELOLAAN SAMPAH PLASTIK DI PULAU PRAMUKA - Nike Vonika; Versanudin Hekmatyar (Politeknik Kesejahteraan Sosial Bandung, 2021)
As the population increases from year to year and is accompanied by a high intensity ofhuman activities, resulting in an increase in the amount of waste piles. Good wastemanagement and processing is currently still very minimal so that it has an impact onenvironmental pollution which in turn affects the sustainability of human life. Meanwhile,environmental factors are one of the determining factors in determining the quality ofpeople's lives. This study describes qualitatively the process of community empowermentrelated to handling environmental problems, namely waste management, especially plasticwaste on Pramuka Island. This empowerment is a collaboration between the Get PlasticFoundation and the Green Literacy House in building a waste management system andinvolving the community as a whole. First, waste handling is carried out by processingplastic waste into fuel (diesel) using a pyrolysis machine developed by Get Plastic. Second,by socializing and educating the public so that they have awareness in protecting theenvironment. The result of the empowerment carried out is that Pramuka Island cansignificantly reduce its plastic waste because it can be processed into energy that can be useddirectly.